2022
DOI: 10.3897/jhr.90.78581
|View full text |Cite
|
Sign up to set email alerts
|

Nesting biology of Trypoxylon petiolatum Smith, 1858 (Crabronidae), a cavity-nesting solitary wasp new to Europe

Abstract: We report on the discovery of the spider-hunting wasp Trypoxylon petiolatum (Crabronidae) nesting in three localities in the Province of Girona (Catalonia, NE Spain) in 2019 and 2021. This species is native to eastern Asia and has not previously been reported from Europe. We provide a detailed description of the species, as well as information on its nest architecture, cocoon shape, the identity of the spiders captured to provision the nests, and mortality rates, including parasitism by a native cleptoparasiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…Most Trypoxylon species construct their nests in pre-existing cavities, such as holes in wood, bamboo and other plant stems and in abandoned mud nests of other wasps. Use of trap nests is common in Trypoxylon and has been reported for various species, such as T. carinatum , T. frigidum , T. kolazyi , T. clavatum , T. collinum , T. lactitarse and T. tridentatum (see Krombein (1967) ); T. deceptorium , T. clavicerum , T. figulus and T. scutatum (see Kazenas (2001) ); and T. bicolor (see Vicens et al (2022) ). In contrast, several species in the genus (the subgenus Trypargilum ) construct their nests with mud and are, thus, called pipe-organ wasps, for example T. monteverdeae (see Brockmann (1992) ) and T. politum (see Brockmann and Grafen (1992) ).…”
Section: Discussionmentioning
confidence: 99%
“…Most Trypoxylon species construct their nests in pre-existing cavities, such as holes in wood, bamboo and other plant stems and in abandoned mud nests of other wasps. Use of trap nests is common in Trypoxylon and has been reported for various species, such as T. carinatum , T. frigidum , T. kolazyi , T. clavatum , T. collinum , T. lactitarse and T. tridentatum (see Krombein (1967) ); T. deceptorium , T. clavicerum , T. figulus and T. scutatum (see Kazenas (2001) ); and T. bicolor (see Vicens et al (2022) ). In contrast, several species in the genus (the subgenus Trypargilum ) construct their nests with mud and are, thus, called pipe-organ wasps, for example T. monteverdeae (see Brockmann (1992) ) and T. politum (see Brockmann and Grafen (1992) ).…”
Section: Discussionmentioning
confidence: 99%
“…Cette espèce vient s'ajouter aux quatre espèces de Sphéciformes introduites en France (le divelec, 2022). Tenant compte de l'introduction récemment signalée de Trypoxylon petiolatum Smith, 1858, en Espagne et d'Isodontia nigella (Smith, 1856) en Crimée, douze espèces exotiques sont actuellement établies ou vraisemblablement établies en Europe (le divelec, 2022 ;vicens et al, 2022 ;Fateryga et al, 2023). Les introductions de Sphéciformes se multiplient en Europe et il ne serait pas surprenant d'en observer d'autres en France à l'avenir.…”
Section: Discussionunclassified
“…Preceding studies [3,6,[18][19][20][21][22][23][24][25][26] showed T. petiolatum using old mud nests of other wasps and trap nests. In the present study, T. petiolatum using man-made holes for the nesting site is recorded for the first time.…”
Section: Trypoxylon Petiolatum F Smithmentioning
confidence: 99%
“…Trypoxylon petiolatum F. Smith is one of wasps of the genus Trypoxylon widely distributed in the Oriental region. It is also recorded in both the Palearctic region (China partly, Korea, Japan and Spain) and Hawaii islands [17,18]. The nesting habits of the wasp have been studied by a large number of authors such as: Horne [3], Rudow [6] and Richards [19] in India (as Trypoxylon rejector F. Smith); Barthélémy [20,21] in Hong Kong; Ma [22] in China (as Trypoxylon obsonator (F. Smith); Yasumatsu [23], Nambu [24,25] and Tsuneki [26] in Japan (as Trypoxylon obsonator F. Smith); and Vicent et al, [18] in Spain.…”
Section: Introductionmentioning
confidence: 99%